Crack path and threshold condition for small fatigue crack growth in annealed carbon steels under fully-reversed torsional loading. (August 2019) - Endo, M.; Yanase, K.
Highlights: Torsional fatigue tests were carried out near the fatigue limit for annealed carbon steels with ferrite-pearlite microstructures. Shear-mode fatigue cracks tended to propagate in the soft ferrite phase, avoiding the hard pearlite phase. The interior geometry of fatigue cracks were observed by precise polishing of the specimens. The torsional fatigue limit is determined by the threshold condition for continuous propagation of a macroscopic Mode I branched crack. Abstract: Torsional fatigue tests at an R of −1 were carried out near the fatigue limit, using smooth, round-bar specimens of annealed carbon steels with banded ferrite/pearlite and isotropic ferrite/pearlite structures. Precise polishing of the specimens made it possible to observe the interior geometry of fatigue cracks. While the crack-plane was macroscopically of shear-mode, it was irregular microscopically, bearing many kinked and branched cracks. Based on calculation of the stress intensity factor for propagating and non-propagating cracks, it was concluded that the torsional fatigue limit was determined by the threshold condition for continuous Mode I propagation into the ferrite/pearlite structure.